The Determinants of Eating Attitudes among Adult Individuals - Siti Hajar Samsu; Nelson Lajuni; Sharon Tan@Rebecca; Jati Kasuma Ali; Hylmee Matahir; Audrey Liwan (Malaysian Consumer and Family Economics Association (MACFEA), 2023)
Obesity costs the public health system money. The WHO estimates that Non-Communicable Diseases kill 73 per cent of Malaysians (NCD) yearly. High blood pressure, high cholesterol, low fruit and vegetable intake, obesity, inactivity, and cigarette use are the most significant NCD risk factors. Unhealthy diets and sedentary lifestyles cause most NCDs, which can be prevented. Thus, this study examines the determinants of adult eating attitudes in selected Sabah and Sarawak cities. This study was carried out empirically through a structured questionnaire using a purposive sampling method. A total of 148 respondents were involved in a survey questionnaire, and the collected data was then analysed using SmartPLS 4.0 software. This study has implications for multiple stakeholders, including consumers, restaurant operators, hospitality managers, brand managers, the government, and society. The study's findings show that life activities, wellbeing, and life satisfaction influence the eating attitudes of adult individuals. The results should drive the government's policies on responsible food service advertising and promoting a healthy lifestyle to combat obesity in Malaysia, notably in Sabah and Sarawak. At the same time, a proper public health care system ensures the community's long-term well-being.